Implementasi Ujian Nasional Berbasis Komputer (UNBK) Di SMA Parulian 1 Medan - Shintia Devi Simbolon; Abdul Kadir; Irwan Nasution (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
This study aims to determine the Implementation of UNBK in Parulian 1 High School in Medan 2016/2017 Academic Year and to know the Implementation of UNBK in 2016/2017 Academic Year in Parulian 1 High School in Medan. In research using a qualitative descriptive approach that is a research method that requires in-depth understanding and focus on the implementation of the Computer-Based National Examination (UNBK) in the 2016/2017 Academic Year. The results of the study that the implementation of computer-based national exams (UNBK) in Parulian 1 Medan Private High School in the 2016/2017 academic year were reviewed from 6 indicators of Van Meter Van Horn theory implementation which included: (a) Standards and objectives of policy objectives, (b) Resources , (c) Characteristics of implementing organizations, (d) Communication between related organizations and implementation activities, (e) Disposition or attitude of implementers, and social, economic political environment shows Implementation of computer-based national exams (UNBK) at Parulian Private High School 1 Medan in the 2016/2017 Academic Year was constrained by facilities and infrastructure and there was no training related to the implementation of UNBK so that the Private High Schools joined the Chairperson of Rayon as a pilot school for the next school year. The conclusion that researchers obtained The implementation of computer-based national exams (UNBK) in Parulian 1 Medan Private High School in the 2016/2017 school year was constrained by facilities and infrastructure and there was no training related to the implementation of UNBK.